(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
This study aims to examine the risks faced by organizations by integrating both theoretical and applied dimensions, in light of the increasing intensity of economic and organizational changes. The first section addresses the theoretical framework of risk by clarifying the concept of risk and its key related terms, identifying its various types—both financial and non-financial—and analyzing the causes of risk emergence and the contributing factors. This section also reviews the main risk measurement tools and the methods used for risk identification and assessment. The second section focuses on analyzing previous studies related to risk management by presenting their key findings and deriving the most prominent prevailing research trends. In addition, the study discusses several modern quantitative techniques used to measure and identify organizational risks, such as risk analysis and wavelet analysis, highlighting the role of these techniques in improving measurement accuracy and enhancing risk forecasting. The study concludes that the adoption of advanced analytical methods contributes significantly to supporting the decision-making process and strengthening organizations’ ability to effectively manage risks, thereby achieving organizational stability and performance efficiency.